Frankfurt am Main, Deutschland. Die Feldforschungsdatenbank der RGK – Ein Überblick zu den Ausgrabungen und Prospektionen. Die Arbeiten der Jahre 2019 und 2020 - Kohle, Maria; Hohle, Isabel A. (e-Forschungsberichte des DAI, 2021)
Almost 20 years ago, on the occasion of the 100th anniversary of the RGK, a comprehensive contribution to the field research was published in the reports of the RGK. The RGK field research database, developed in advance, formed the basis of the maps and diagrams shown there. The adjustments, updates, and additions made to this database, especially since 2019, as well as the planning for the migration to a PostgreSQL database and links to iDAI.world formats, inspired to summarize the field research of the RGK again and to take a look at the developments in the methods of field research. The following contribution is to be understood as a report presenting the ongoing works around the RGK field research database.